Hallucinations of an Interior - Drożyński, Charles (Scenari, 2024)
The work of Deleuze and Guattari is often presented in terms of spatial ontology as it explores relationality between fragments that constitute the real. As such, it is readily accepted as a theoretical framework for architects and geographers who use this approach to develop their consecutive fields. Similarly to these disciplines, the work of the duo is permeated with imagery that help in representing concepts they are exploring in a soft and non-abrasive way. While recognising the capacity of imagery in representing spatial concepts they curiously avoid architectural drawings but venture into a different kind of illustrations always describing them or presenting their own way of producing adequate diagrams. In one instance, the imagery that they described in a crucial moment of focussing on a key concept for the pair showcases a metaphysical reading of the world – one that likely stands at the border between the virtual and the actual. These are the renderings of Robert Gie. A reading of the comparison between his renderings and the architectural drawing convention which is lacking in the texts of Deleuze and Guattari, can help reconcile the concepts in the texts which discuss desire and problematic ideas of interiority.